Morphological reconstruction of the Kimberley-Elsburg series, with special reference to the Kimberley group of sediments in the East Rand basin - De Jager, F. S. J (Stellenbosch : Stellenbosch University, 2012)
Thesis (DSc.)--Stellenbosch University, 1952.